The Mars Oxygen Visible Dayglow: A Martian Year of NOMAD/UVIS Observations. Issue 6 (7th June 2022) - Soret, L.; Gérard, J.‐C.; Aoki, S.; Gkouvelis, L.; Thomas, I. R.; Ristic, B.; Hubert, B.; Willame, Y.; Depiesse, C.; Vandaele, A. C.; Patel, M. R.; Mason, J. P.; et al.
Abstract: The Ultraviolet and Visible Spectrometer Ultraviolet (UVIS UV) and Visible Spectrometer channel of the Nadir and Occultation for MArs Discovery spectrometer aboard the ExoMars Trace Gas Orbiter has made limb observations of the Martian dayglow during more than a Martian year. Two pointing modes have been applied: (a) In the inertial mode, the spectrometer scans the atmosphere twice down to near the surface and provides altitude profiles of the dayglow; (b) in the tracking mode, the atmosphere is scanned at varying latitudes at a nearly constant altitude through the entire observation. We present a statistical study of the vertical and seasonal distribution of the recently discovered oxygen green and red lines at 557.7 nm and 630 nm. It indicates that the brightness of the green line emission responds to changes in the Lyman‐α flux. The peak altitude of the green line emission increases seasonally when the Sun‐Mars distance decreases. The lower peak of the green line statistically drops by 15–20 km between perihelion and aphelion at mid‐to high altitude. The main lower peak intensity shows an asymmetry between the two hemispheres. It is significantly brighter and more pronounced in the southern hemisphere than in the north. This is a consequence of the stronger Lyman‐α solar flux near perihelion. The second component of the oxygen red line at 636.4 nm is also detected for the first time in the Martian atmosphere. A photochemical model is used to simulate the variations of the green dayglow observed along limb tracking orbits. Plain Language Summary: The Ultraviolet and Visible Spectrometer (UVIS) instrument aboard the ExoMars Trace Gas Orbiter made it possible to observe the visible emissions that occur on the dayside of the Mars atmosphere during more than a Martian year. Among them, the emissions of the oxygen called "green line" and "red line" (because of their wavelength of 557.7 nm and 630 nm, respectively), which are analyzed over time and can be used as proxies to study the changes in the upper atmosphere of Mars. We show that these emissions occur at higher altitudes and are brighter when Mars is closer to the Sun. We also show evidence of the presence of the second component of the red line at 636.4 nm, which confirms the identification of the recently discovered 630 nm emission. While the green line is composed of two peaks near 80 and 120 km, the red line limb brightness presents a broad peak near 140 km. Finally, we show that a photochemical model simulates the UVIS data very well. Key Points: Nadir and Occultation for MArs Discovery/Ultraviolet and Visible Spectrometer limb observations of the green line dayglow show large seasonal variability in both the peak altitude and brightness We bring evidence of the presence of the second component of the oxygen red line at 636.4 nm Model simulations confirm that the Sun‐Mars distance controls the altitude and the brightness of both oxygen emissions